2020
DOI: 10.1155/2020/4980618
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Treadmill Training Programme in Improving the Postural Balance on Institutionalized Older Adults

Abstract: Background. Institutionalized older adults have increased gait and balance impairment compared with community-dwelling older adults. The use of the treadmill for the rehabilitation process has been studied in different groups, but not in the institutionalized elderly. Objectives. The objective of this study was to assess the effects of a treadmill walking workout program on the postural balance of institutionalized older adults. Methods. Postural balance was assessed by the Berg Balance Scale (BBS), Short Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…First, most of the included studies in this review contrasted RGPT with regular treadmill training (Klamroth et al, 2016 ; Steib et al, 2017 ; Gimmon et al, 2018 ; Rieger et al, 2020 ). Treadmill training alone has shown strong positive effects on gait speed and stride length in several populations, including frail older adults and PwPD (Van Ooijen et al, 2013 ; Mehrholz et al, 2016 ; Ni et al, 2018 ; Pereira et al, 2020 ). The Cochrane review conducted by Mehrholz et al ( 2016 ) showed substantial effects of treadmill training in PwPD when compared to other interventions (e.g., stretching, dancing, resistance training, conventional therapy) on both gait speed [Mean difference (post-pre) = 0.09 m/s; 95% CI = 0.03, 0.14; p = 0.001] and stride length [Mean difference (post-pre) = 0.05 m; 95% CI = 0.01, 0.09; p = 0.01] without increased drop-out rates or adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…First, most of the included studies in this review contrasted RGPT with regular treadmill training (Klamroth et al, 2016 ; Steib et al, 2017 ; Gimmon et al, 2018 ; Rieger et al, 2020 ). Treadmill training alone has shown strong positive effects on gait speed and stride length in several populations, including frail older adults and PwPD (Van Ooijen et al, 2013 ; Mehrholz et al, 2016 ; Ni et al, 2018 ; Pereira et al, 2020 ). The Cochrane review conducted by Mehrholz et al ( 2016 ) showed substantial effects of treadmill training in PwPD when compared to other interventions (e.g., stretching, dancing, resistance training, conventional therapy) on both gait speed [Mean difference (post-pre) = 0.09 m/s; 95% CI = 0.03, 0.14; p = 0.001] and stride length [Mean difference (post-pre) = 0.05 m; 95% CI = 0.01, 0.09; p = 0.01] without increased drop-out rates or adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…These constituents of balance training could be combined in the same task (e.g., head-turning while standing with feet together on a foam pad) according to the participant’s ability. As an exercise for improving dynamic balance during walking, balance training included walking on a treadmill at alternating speeds ( 29 ). Finally, leg press and chest press machines were used for training trunk balance during ballistic movements of the upper and lower limbs, respectively ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…One of the key areas of investigation is the impact of treadmill training on postural stability in the elderly. This aspect is crucial because maintaining a good postural balance is fundamental to performing everyday activities and reducing the risk of falls, which are a significant health concern in this age group (Pereira et al, 2020(Pereira et al, , 2021Hirjaková et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nørgaard et al (2023) ingeniously introduced perturbation-based balance training on a treadmill, culminating in a compelling reduction in fall rates among community-dwelling older adults. A confluence of results fromPereira et al (2020Pereira et al ( , 2021,Pirouzi et al (2014), andTargino et al (2012) further amplifies this narrative, unveiling substantial improvements in postural balance and a significant upswing in the quality of life among institutionalized elderly individuals, further emphasizing the holistic impact of treadmill interventions.The narrative extends to older individuals grappling with neurological conditions, prominently Parkinson's disease and hemiparesis Luna et al (2020). masterfully unraveled the positive implications of treadmill training on gait patterns in Parkinson's disease, shedding light on the potential for rehabilitation and functional recovery in this population.…”
mentioning
confidence: 96%